Identity as Life & Death in My Name Is Okoro - Onyekachi Peter Onuoha; Lilian Onyinye Ohanyere (Tamaddun Life, 2021)
History provides the framework for literary production and the corroboration of historical controversies. Identity is implicated in the controversy of My Name is Okoro. This paper, through the application of new criticism as an analytic framework, examines identity as a thin line between life and death in My Name is Okoro. It further examines how identity is self-definition and survival. Many scholars have focused their literary analysis on the effects of the Nigerian Civil War without paying attention to the role of naming and identification during the war. This study also highlights that in times of crisis, identity protect the individuals who are associated with the side that wills more physical and military power. Identity is factor that affects the survival of individual in the society. This paper concludes that those of minority extraction as well as the Igbo of the Eastern region suffered greatly as a result of their identity in My Name is Okoro.